Acute appendicitis revealed by an abscess of the anterior abdominal wall: A case report - Bannar B; Mahad R; Boutakioute B; Ouali Idrissi M; Cherif Idrissi Ganouni N; Maaroufi Fathiallah EL; EL Boukhfaoui M; Rabbani K; Louzi A; Finech B (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2020)
Introduction: Appendicitis is a common cause of acute abdomen; however the classic clinical signs are not often present, which can be manifested by numerous complications, but the revelation by a parietal collection remains unusual, its diagnosis can be challenging.  Presentation of case: We describe the case of a 31 years old man, who complains for pain of the right flank. The clinical examination objective an erythematous and painful swelling of the right iliac fossa, the abdominal ultrasound has objectified a collection of the right flank and right iliac fossa, The CT Scan of the Abdomen/Pelvis found a voluminous collection of soft tissues of the right anterolateral abdominal and pelvic wall, hypo dense and heterogeneous, containing air, The surgical exploration objectified a huge purulent collection with subcutaneously ceacum and appendage suppurated and perforated. Conclusion: The onset of an abdominal wall abscess without a known cause needs to be thoroughly investigated, with consideration of a subjacent abdominal cause and appendicitis.